Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
- x = -2
- x = -3
Step-by-step explanation:
[tex] \bf {x}^{2} + 5x + 6 = 0[/tex]
Write the equation in factored form.
[tex]\bf (x + 2)(x + 3) = 0[/tex]
Separate equations, and set each factor to zero.
[tex]\bf x + 2 = 0[/tex]
[tex]\bf x + 3 = 0[/tex]
Rearrange and isolate the variable to find the solutions
[tex]\bf x = - 2[/tex]
[tex]\bf x = - 3[/tex]
------------------------------------
Answer:
x=-3 x=-2
Step-by-step explanation:
x^2 +5x+6 =0
We need to factor the equation
What two numbers multiply to 6 and add to 5
3*2 = 6
3+2 =5
(x+3)(x+2)
Using the zero product property
x+3 =0 x+2 =0
x=-3 x=-2
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.